2 states [videorecording (DVD)] : one love-- - Varman, Abhishek; Kapoor, Arjun; Bhatt, Alia, 1993- (Reliance Big Entertainment, 2014)
Punjabi boy and Tamilian girl discover love on their college campus. However, their diverse cultures make its culmination a challenge.